APPROACHES TO ENHANCING THE ECONOMY OF KARAKALPAKSTAN - Isakov Janabay Yakypbayevich; Zhubanova Bayramgul Aymuratovna; Maxamatdinov Miyirbek Polatovich (Journals Park Publishing, 2025)
This article examines key strategies for developing the economy of Karakalpakstan, an autonomous republic within Uzbekistan. The region is rich in natural resources and cultural heritage but faces significant economic challenges, particularly due to the ecological disaster of the Aral Sea. The study identifies crucial sectors for growth, including agriculture, industry, tourism, and environmental restoration. It emphasizes the need for modern infrastructure, sustainable practices, and investment in human capital to ensure long-term economic development. By implementing these strategies, Karakalpakstan can unlock its economic potential, improve living standards, and contribute to the broader economic growth of Uzbekistan.
Keywords: Karakalpakstan, economic development, agriculture, industrial growth, tourism, environmental restoration, infrastructure, sustainable development, green economy, economic strategies, Uzbekistan.